Extracting 21 cm signal by frequency and angular filtering. (August 2018) - Huang, Qi-Zhi; Wu, Feng-Quan; Ansari, Reza; Chen, Xuelei
Abstract: Extracting the neutral hydrogen (HI) signal is a great challenge for cosmological 21 cm experiments; both the astrophysical foregrounds and receiver noise are typically several orders of magnitude greater than the 21 cm signal. However, the different properties of the 21 cm signal, foreground and noise can be exploited to separate these components. The foregrounds are generally smooth or correlated over the frequency space along a line of sight (LoS), while both the 21 cm signal and noise vary stochastically along the same LoS. The foreground can be removed by filtering out the smooth component in frequency space. The receiver noise is basically uncorrelated for observations at different times, hence for surveys it is also uncorrelated in different directions, while the 21 cm signal, which traces the large scale structure, is correlated up to certain scales. In this exercise, we apply Wiener filters in frequency and angular space to extract the 21 cm signals. We found that the method works well. Inaccurate knowledge about the beam could degrade the reconstruction, but the overall result is still good, showing that the method is fairly robust.